2015
DOI: 10.1155/2015/718786
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutationsin the Transcriptional Activator Domain of the Human TBX20 in Patients with Atrial Septal Defect

Abstract: Background. The relevance of TBX20 gene in heart development has been demonstrated in many animal models, but there are few works that try to elucidate the effect of TBX20 mutations in human congenital heart diseases. In these studies, all missense mutations associated with atrial septal defect (ASD) were found in the DNA-binding T-box domain, none in the transcriptional activator domain. Methods. We search for TBX20 mutations in a group of patients with ASD or ventricular septal defect (VSD) using the High Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that TBX20 polymorphisms are closely related to the occurrence and development of CHD in children Kwiatkowski et al, 2015;Lin et al, 2015;Monroy-Muñoz et al, 2015), results of this study were in concordance with those of previous studies. TBX20 SNP loci that have been reported thus far include: rs6950175 and rs3999941.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that TBX20 polymorphisms are closely related to the occurrence and development of CHD in children Kwiatkowski et al, 2015;Lin et al, 2015;Monroy-Muñoz et al, 2015), results of this study were in concordance with those of previous studies. TBX20 SNP loci that have been reported thus far include: rs6950175 and rs3999941.…”
Section: Discussionsupporting
confidence: 93%
“…An in vivo study has also indicated that by using RNAi technology, knock down of TBX20 or expression of TBX20 mutants causes mammalian heart disease . Furthermore, human studies have shown that missense mutations in the TBX20 gene is closely related to the occurrence of congenital heart disease in children (Monroy-Muñoz et al, 2015). However, the role of TBX20 in a Chinese population, especially children with congenital heart disease, needs to be clarified .…”
Section: Introductionmentioning
confidence: 99%
“…By whole-exome sequencing of a three-generation family with ASD, Liu et al [44] detected a novel TBX20 mutation (p.D176N) co-segregated with ASD. By genetic analysis of TBX20 in 38 patients with ASD or ventricular septal defect (VSD), Monroy-Muñoz et al [45] discovered three missense mutations (p.Y309D, p.T370P and p.M395R) in three ASD patients, respectively, and found 12 SNPs previously listed in SNP database, including F256L (rs3999941). Besides, TBX20 mutations were also implicated with VSD and/or double outlet right ventricle [23,38].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic factors may have important roles in the development of CHD, and TOF and VSD may have similar molecular mechanisms [ 39 ]. But other scholars [ 40 ] have reported that there were some novel mutations in the transcriptional activator domain of the human TBX20 with ASD.…”
Section: Discussionmentioning
confidence: 99%